Photochemically synthesized gold nanoparticles conjugated with Boswellic acid inhibit alpha synuclein aggregation and delay fibrillation kinetics - Masoumeh Gharb; Farima Mozafari; Payam Arghavani; Ali Akbar Saboury; Gholamhossein Riazi (Scientific Reports)
Abstract Neurodegenerative disorders are characterised by the gradual degeneration and death of neurons in distinct brain regions. In Parkinson’s disease (PD), a key pathological hallmark is the aggregation of misfolded α-synuclein (α-Syn) into neurotoxic fibrils. Although natural products such as Boswellic acids (BAs) from Boswellia serrata exhibit therapeutic potential, their clinical application is limited by poor pharmacokinetic properties. To address this, we investigated BAs conjugated to gold nanoparticles (GNPs) to enhance bioavailability and therapeutic potential. Both covalent and noncovalent β-Boswellic acid to GNPs (GNP-BA) conjugates were synthesized and evaluated for their effects on α-Syn fibrillation in vitro. The spherical GNPs (< 32 nm) were successfully characterized via high-resolution transmission electron microscopy (HR-TEM) and field emission scanning electron microscopy (FESEM). Conjugation of BA was confirmed by UV–Visible and Fourier-transform infrared (FTIR) spectroscopies. Thioflavin T (ThT) assay and atomic force microscopy (AFM) analyses demonstrated that noncovalently bound GNP-BAs significantly inhibited α-Syn fibril formation. Our findings reveal that both synthesis and conjugation strategies significantly influence the anti-aggregation behaviour of GNPs. Notably, photochemically synthesised GNP-BAs exhibited superior biofunctionality. This work introduces a dual-functional nanoplatform that enhances BA bioavailability while effectively inhibiting α-Syn aggregation, offering translational potential for real-world therapeutic development in PD and related synucleinopathies.